2023
DOI: 10.3390/ijerph20054442
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Technology Acceptance on Blended Learning Satisfaction: The Serial Mediation of Emotional Experience, Social Belonging, and Higher-Order Thinking

Abstract: This study explored the relationship between technology acceptance and learning satisfaction in the context of blended learning, with a particular focus on the mediating effects of online behaviors, emotional experience, social belonging, and higher-order thinking. A total of 110 Chinese university students participated in this study and completed a questionnaire at the end of 11 weeks of blended learning. The results demonstrate that technology acceptance directly and indirectly relates to blended learning sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 75 publications
0
5
0
1
Order By: Relevance
“…The factors of social media acceptance in blended learning were also researched by [20], with the results of their research being that sharing knowledge has a significant positive impact on the perceived benefits and perceived ease of use of the e-learning system, social media features have an impact significant positive impact on the perceived usefulness and perceived ease of use of the e-learning system, and motivation and use have a significant positive effect on the perceived usefulness and perceived ease of use of the e-learning system. This shows that social media has a positive impact on blended learning [19], [20], but research by [15], [16], [17] has not shown significant use of social media in relation to learner abilities to use social media as a source of information.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…The factors of social media acceptance in blended learning were also researched by [20], with the results of their research being that sharing knowledge has a significant positive impact on the perceived benefits and perceived ease of use of the e-learning system, social media features have an impact significant positive impact on the perceived usefulness and perceived ease of use of the e-learning system, and motivation and use have a significant positive effect on the perceived usefulness and perceived ease of use of the e-learning system. This shows that social media has a positive impact on blended learning [19], [20], but research by [15], [16], [17] has not shown significant use of social media in relation to learner abilities to use social media as a source of information.…”
Section: Introductionmentioning
confidence: 88%
“…However, researchers found that efforts to implement it in Indonesia still needed to align with what was expected. Recent research conducted by [19] in his study examined the relationship between technology acceptance and learning satisfaction in a blended learning context, focusing on the mediating effects of online behavior, emotional experience, social belonging, and higher-order thinking. This research shows that technology acceptance has a significant direct relationship with learning satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trabajos realizados en Indonesia (Mustikasari et al, 2021) y China (Pei et al, 2020, en los sectores de entretenimiento, tecnología y ropa, encontraron que la experiencia con el producto influye sobre la satisfacción con la compra en línea. También, diferentes estudios en los ámbitos del aprendizaje en línea (Chen et al, 2023), laboral (Lindner et al, 2021, y turístico (Ratnasari et al, 2021) han identificado que la experiencia emocional incide positiva y significativamente sobre la satisfacción. Finalmente, existe evidencia empírica que apunta que la experiencia con el sitio web favorece la satisfacción del consumidor; tal es el caso de un trabajo realizado con minoristas en línea de comercio de moda en España (Gutiérrez Rodríguez et al, 2020).…”
Section: Conciencia Ambiental Y Experiencia De Compra En Líneaunclassified
“…The first is the completion of the period of coverage of the JetIQ electronic ecosystem of all educational and scientific units of VNTU. The second relates to the previously mentioned need for a complete transition to the online mode of the educational process due to the introduction of a blanket lockdown in Ukraine (Chen et al, 2023). Thus, there is every reason to claim that at the beginning (and amid the war) of the 2022/2023 academic year, the JetIQ electronic ecosystem has become the primary tool used to manage the educational activities of VNTU.…”
Section: Development Of Jetiq Academic Management Tools At Vntumentioning
confidence: 99%